1990
DOI: 10.1177/095646249000100603
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Diseases and Rape: The Experience of a Sexual Assault Centre

Abstract: Epidemiological data and rates of sexually transmitted diseases (STDs) are presented from a group of 90 women screened following rape. Forty-eight (53%) women knew their assailant. In 6 cases multiple assailants were involved. In 21 (23%) rapes weapons were used. Of 47 women examined within 48 hours of rape, 17 (36%) had evidence of genital trauma. Anal injury was common (8 of 11, 73%) in those reporting anal intercourse. Anal assault (17 of 90, 19%) and oral assault (16 of 90, 18%) commonly accompanied rape. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 14 publications
2
13
1
Order By: Relevance
“…When evaluating whether the assailant was known to the attacker at all, more than 50% of sexual assault victims of either sex knew their attackers; this is consistent with other literature for female sexual assaults. 7,12,22 However, in our study, it appeared more than twice as likely that the female victim would not know her assailant, compared with the male victim. This could be related to the small stature and physical strength characteristics of females compared with males, which encourages physical attack on females by sexually aggressive males vs attacks on other males by sexually aggressive males.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…When evaluating whether the assailant was known to the attacker at all, more than 50% of sexual assault victims of either sex knew their attackers; this is consistent with other literature for female sexual assaults. 7,12,22 However, in our study, it appeared more than twice as likely that the female victim would not know her assailant, compared with the male victim. This could be related to the small stature and physical strength characteristics of females compared with males, which encourages physical attack on females by sexually aggressive males vs attacks on other males by sexually aggressive males.…”
Section: Discussionmentioning
confidence: 43%
“…Cultures for these organisms were generally not done because it is believed that cultures taken within the first few days after a sexual assault are the result of the victim's previous sexual activity. 12,13 Twenty-six of 27 patient encounters with the EP were definitely offered prophylactic antibiotics and 23 of 26 accepted. Therefore, except for one missed opportunity, the potential prevention of these two diseases was well done.…”
Section: Discussionmentioning
confidence: 99%
“…There is consistent evidence in literature associating HPV infection in cases involving sex crimes. In adult women who suffer sexual violence, its incidence ranges between 2% and 40% [40][41][42] . A longitudinal study, controlled and randomized, with 665 American young women found that those with a history of sexual abuse in the past 12 months were 4.5 times more likely to test positive for HPV 16 or 18 in the cervix, suggesting sexual abuse as a risk factor for infection by HPV 37 .…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Reported descriptive data on the victims and the assaults are, for the main part, at the Danish level [18][19][20][21][22][23][24][25][26] except peaks at 67% strange assailants, 17 90% exposed to physical coercion, 14 92% completed intercourses, 27 genital lesions in 68%, 28 and body lesions up to 89% of the cases. 29 Only few studies have reported annual incidences and they have been very diverse because of various definitions of sexual violence, different year of study, different settings, and different inclusion criteria.…”
Section: Introductionmentioning
confidence: 99%